Upaya Meningkatkan Hasil Belajar Siswa dalam Mata Pelajaran IPA pada Materi Rangkaian Listrik melalui Metode Eksperimen pada Siswa Kelas VI/A Semester I SDN 10 Penatoi Kota Bima - Sastrawati, Ening (Universitas Nggusuwaru, 2023)
This study is motivated by the low learning outcomes in the Natural Science (IPA) subject at SDN 10 Penatoi Kota Bima, particularly regarding the topic of electrical circuits, which is attributed to the implementation of teacher-centered conventional learning methods. Therefore, classroom action research (PTK) was conducted to examine and implement an experimental method aimed at improving student learning outcomes. The research subjects were the class VI/A students, consisting of 29 students (11 males and 18 females). The data collection instruments included learning outcome tests, observation sheets for both student and teacher activities, and supporting documents. The research results indicate that the implementation of the experimental method significantly enhanced learning activities, student involvement in the experimental process, and the average post-test scores that met the mastery criteria (a minimum score of 7 and a passing percentage of ≥85%). The implication of this study is that the experimental method is effective in optimizing Natural Science education, thereby producing a more enjoyable and meaningful teaching and learning process